Modulation of Mucin Secretion in the Gut of Young Pigs by Dietary Threonine and Non-Essential Amino Acid Levels - Ewa Święch; Anna Tuśnio; Marcin Taciak; Marcin Barszcz (Animals, 2022)
The aim of the study was to determine the effect of threonine (Thr) and non-essential amino acid (NEAA) levels on mucin secretion and sugar composition of digesta and crude mucin preparations analyzed in different segments of the gut in young pigs. A two-factorial experiment was conducted on 72 pigs using the following factors: Thr level (5.1, 5.7, 6.3 and 6.9 g standardized ileal digestible(SID) Thr/kg) and wheat gluten (WG) level used as a source of NEAA (20.4, 40.4 and 60.4 g WG protein in WG20, WG40 and WG60 diets, respectively). Mucin content was affected only by WG level. Tissue mucin content in the duodenum was higher in WG60 pigs than in WG20 and WG40 pigs, whereas in the middle jejunum was higher in WG40 and WG60 pigs than in WG20 pigs. In contrast, luminal crude mucin content in the proximal colon was lower in WG60 pigs compared to WG40 pigs. The lowest and highest Thr levels reduced arabinose and xylose contents and increased glucose content in ileal digesta. The highest WG level reduced arabinose and xylose contents and increased glucose content in ileal digesta. The lowest WG level increased mannose content in ileal digesta. WG60 level decreased the content of arabinose and galactose compared to lower WG levels in colonic digesta. Arabinose content was higher, while glucose and galactose contents were lower in crude mucin preparations isolated from colonic digesta in pigs fed diets containing the highest Thr level. The content of tissue mucin was higher in the ileum and proximal colon and lower in the duodenum than in the middle jejunum, whereas luminal mucin content was lower in the proximal colon than in the ileum. Ileal digesta contained less arabinose and glucose and more galactose as compared to colonic digesta. In conclusion, no effect of dietary Thr levels on mucin secretion in the gut of young pigs was found. Wheat gluten added to the diet with adequate Thr content positively affected mucin secretion only in the duodenum and middle jejunum.